The Level of Basic Futsal Skills Among Elementary School Students Participating in Extracurricular Futsal Activities at State Elementary School 04 Jeumpa, Academic Year 2025/2026 - dedi saputra; Rahmat Hidayat; Muhammad Reza Reza; Imam Taufik Harahap; Novida Humaira (CV Abid Abadi Jaya, 2026)
This study aimed to determine the level of basic futsal skills among students participating in the futsal extracurricular program at State Elementary School 04 Jeumpa in the 2025/2026 academic year. A quantitative descriptive design was used. The sample comprised 20 students selected through total sampling, so all extracurricular participants became research subjects. Data were collected using a basic futsal skills test covering passing, dribbling, shooting, and ball control. The data were analyzed descriptively using mean, percentage, frequency, minimum and maximum scores, and standard deviation. The results showed that students’ overall basic futsal skills were in the moderate category, with a mean score of 57.13. In detail, 2 students (10.0%) were categorized as very good, 5 students (25.0%) as good, 9 students (45.0%) as moderate, 3 students (15.0%) as poor, and 1 student (5.0%) as very poor. Each skill component also tended to fall in the moderate category. These findings indicate that students have sufficient basic futsal ability, but their technical performance still needs to be improved through structured, continuous, and age-appropriate training. Therefore, teachers and coaches should prioritize repetitive drills, game-based practice, and regular evaluation to support better mastery of fundamental futsal techniques in extracurricular sessions throughout the school year